Preparation of cationic proteoliposomes using cell-free membrane protein synthesis: the chaperoning effect of cationic liposomes. Issue 48 (4th August 2020) - Ando, Mitsuru; Sasaki, Yoshihiro; Akiyoshi, Kazunari
Abstract : The preparation method of cationic proteoliposomes is established using a cell-free membrane protein synthesis in the presence of cationic liposomes. Abstract : Membrane protein reconstituted cationic liposomes are constructed using cell-free membrane protein synthesis in the presence of cationic liposomes. The chaperon effect of cationic liposomal membrane assists in folding the functional conformation of membrane protein. This preparation method enables the provision of the usage of proteoliposomes for drug delivery.